Pengaruh Sosial Media Marketing, Store Atmosphere, Kualitas Pelayanan terhadap Keputusan Pembelian di Titik Tuju Coffe & Roastery - Adelia Azizah Arifin Putri; Endah Kurniawati; Nuril Aulia Munawaroh (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to analyze the effects of social media marketing, store atmosphere, and service quality on consumers’ purchasing decisions at Titik Tuju Coffee & Roastery in Kediri City. The background of this research is based on the increasing competition in the coffee shop industry, which requires business actors to implement effective marketing strategies, create a comfortable store atmosphere, and provide high-quality services to influence consumers’ purchasing decisions. The research method used is a quantitative approach with data collection conducted through questionnaires. The research sample consisted of 120 respondents who were consumers of Titik Tuju Coffee & Roastery, selected using a simple random sampling technique. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that, partially, social media marketing, store atmosphere, and service quality have a positive and significant effect on purchasing decisions. In addition, the simultaneous test results show that the three independent variables collectively have a positive and significant effect on consumers’ purchasing decisions. The coefficient of determination indicates that most of the variation in purchasing decisions can be explained by these three variables. This study is expected to provide practical contributions for coffee shop managers in designing appropriate marketing strategies and improving service quality and store atmosphere to encourage consumers’ purchasing decisions.